The pilates body - Siler, Brooke, 1968- (Harmony, 2025)
"Since its publication in 2000, The Pilates Body has helped hundreds of thousands readers around the world discover the power of Pilates. Originally developed in the early 1900s by Joseph H. Pilates, it remains the ultimate mind-body fitness system for anyone who wants to build strength, improve flexibility, perfect their posture, reduce aches and pains, and develop a deeper connection with their bodies. In The Pilates Body, Brooke Siler, who trained under Joseph Pilates protégée Romana Kryzanowska, offers a comprehensive program of Pilates exercises that can be done anywhere and anytime with an exercise mat. Siler guides the reader through the principles that form the foundation of Pilates and offers directions for more than fifty exercises. The exercises, categorized by difficulty level, include: Step-by-step photos and instructions, line drawings, and unique visualizations to help you perform the proper movements with the right balance of breath and muscle activation; Modifications for beginners, transitions between exercises to help you move fluidly through your practice, and progressions that keep you moving forward; Troubleshooting tips for avoiding common pitfalls and injury as well as guides for maximizing your results. In this revised and expanded edition, you will find more progressions, variations, and updated cues throughout the exercises. You will also learn how to deepen your Pilates practice in an exciting-new chapter that explores the strengthening and lengthening benefits of incorporating pandiculation-the contraction and relaxation of muscles to discharge muscular tension and foster mobility. Siler explains pandiculation's essential role in your neuromuscular health and how it unlocks more of Pilates's benefits, while offering instructions for pandiculated versions of sixteen matwork exercises to revitalize your body and your practice. Through its warm, concise approach and creative, detailed visuals, The Pilates Body will help you master a movement system that enhances your physical and emotional well-being, no matter your skill level, age, or fitness level"-- Provided by publisher.